Ossifying fibroma in an adolescent boy and his mother: a case report - K., Jaseela T.; V., Priya P.; Sundaram, Sankar (International Journal of Research in Medical Sciences, 2021)
Cemento-ossifying fibroma is a rare benign neoplasm occurring in the tooth bearing areas of mandible and maxilla. Here we report a case of an adolescent boy who presented with swelling in the right side of mandible. It was excised surgically and histopathological diagnosis of cement-ossifying fibroma was made. His mother also had history of cemento-ossifying fibroma 10 years back. This case is being reported for its rare incidence and familial occurrence.